Anatomical Variations of Modiolus in Relation with Vestibular and Cranial Morphology on CT Scans - Caroline Guigou; Raabid Hussain; Alain Lalande; Alexis Bozorg Grayeli (MDPI AG, 2023)
Background: Fundamental knowledge of the anatomy and physiology of the inner ear is necessary to understand otologic diseases and therapeutic strategies. Aim: Evaluate the inter- and intraindividual variability of the modiolar position in relation to vestibular landmarks and cranial morphology on computed tomography scans (CT scan). Methods: Thirty CT scans of normal temporal bones (25 adults, 5 children) were analyzed after multiplanar reconstruction (MPR). The measurements for each ear included the angle of each semicircular canal (SCC) made by a line passing through the chosen plane and a line passing between the apex and the ampulla of the SCC studied and the angle of the modiolus in the transverse and sagittal planes. Results: Intraindividual asymmetries with a moderate to good right/left correlation were observed for the lateral SCC in the transverse plane, posterior SCC in the frontal plane, and the superior SCC in the sagittal plane and for the modiolus in the transverse plane. Conclusions: An anatomical variability in the cochlea, independent of other surrounding anatomical elements, seems to exist, but the SCCs seem to remain symmetrical. Significance: The orientation of the modiolus is an important knowledge to acquire during presurgical planning prior to transmodiolar auditory nerve implantation.